KONSTRUKSI KECANTIKAN IDEAL PEREMPUAN MELALUI IKLAN PRODUK KECANTIKAN DI TELEVISI - Rosana Hariyanti; Lusia Neti Harwati (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
Beauty can be interpreted in many different ways across time and culture. This study aims to discuss the phenomenon of how the ideal beauty standard for women portrayed by three different beauty products commercials (Pond’s, Dove, Biore). Sociological approach related to the social construction of reality and unstructured interview with an advertising practitioner are used as primary methods in this study. The results of this study indicate that the three ads have characteristics in accordance with the policy of each manufacturer. However, these products have a general view on ideal beauty: slim, a pan Asian look, white skin, active, and modern. This concept becomes the ideal of beauty which is coveted by Indonesian women. Television ads accommodate that idealism as a product of marketing strategy, although it does not fit to the physical characteristics of most Indonesian women.